The inheritance and gift taxation - considerations about its nature - Silva, Hugo Manuel Flores (2017)
[Excerpt] In this article, and following political movements and a growing public discussion evidenced on this subject, we address the inheritance and gift taxation in order to ascertain its place in the context of the Portuguese tax system. Aiming this goal, we will consider the Portuguese experience in this area, analyzing the legislative sequence and, where it proves useful, we will consider the adopted solutions within other fiscal systems. Once completed that objective, we will promote a brief analysis of the consequences that arise from such characterization – mainly at the level of its constitutional conformity. […]